Development of a digital pocket book. It is based on Dompu cultural ethnoscience "Ngahi Rawi Pahu." The goal is to strengthen 21st-century science skills. - Devia Sugmawati; Nurul Istiqamah; Nikman Azmin (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this research is to develop a digital pocket book media based on Dompu cultural ethnoscience to strengthen 21st century science skills, which include critical thinking, creative, collaborative, and communication skills. The research method uses Research and Development (R&D) model with Addie step adaptation. Stages of research: needs analysis through interviews and observations on teachers and Junior High School students; digital pocket book content design with integration of local science and culture materials; product development through Android-based software; limited trials and revisions; and evaluation of media effectiveness. Semi-structured interview data collection techniques, participatory observation, media and material validation questionnaires, and student science skills tests. Quantitative descriptive data analysis for validation data and effectiveness tests, and qualitative analysis for interview and observation data. The results showed that the digital pocket book media has a very high feasibility rate, with a validation score of 92.5% and 94.0% material expert media expert. A trial of 60 students showed significant improvements in 21st century science skills, with an average pretest score of 63.4 and posttest of 86.7. Analysis of paired t-tests resulted in a value of t = 14.52 (p < 0.001), showing significant differences before and after the use of media.